ACTION RESEARCH TO SOLVE MUSIC TEACHING PROBLEMS IN THE SCHOOL - Suharto, Suharto (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2000)
ACTION research has been known and regard as one of the new strategy for teachers development in Indonesia. Trough Word Bank Project, for instance, action research has been decided as the secondÂ pilot project and today it has being tried out in eleven provinces in Indonesia, include Central Java.As a ˜special subject, music, has many problems in teaching. It happens for years particularly in classroom. Unfortunately, there is no serious effort of the teachers to look for what the problems are and how to overcome it. They should know that there are many problemsÂ for the students to learn music in the class.The problems of music learning usually happen in the classroom, both for students or for the teachers. However, as if the teachers do not care to the problems and become the problems as a routine duty. The difference of the student music ex-perience problems can influence the learning process. The different background can also influence the quality of the learning process.The music learning in the classroom is a teachers responsibility in which they know how the students learn, the students characteristics, study environment, students' motivations, students progression, etc. To reach a good result of the students achievement need to teachers responsibility efforts to observe, plan, apply, practice, and so on, to get the good way how to the student can learn music well. The way is carried out in many times, for about five to seven or even more then that to achieve a good environment and a good way to teach or how should the students can learn well. To achieve the way above the teacher need to observe trough research. And the properly research to the purpose is action reÂsearch or classroom-based action research (CAR).